2018
DOI: 10.1007/s00406-018-0896-0
|View full text |Cite
|
Sign up to set email alerts
|

Stigma as a barrier to recognizing personal mental illness and seeking help: a prospective study among untreated persons with mental illness

Abstract: It is unclear to what extent failure to recognize symptoms as potential sign of a mental illness is impeding service use, and how stigmatizing attitudes interfere with this process. In a prospective study, we followed a community sample of 188 currently untreated persons with mental illness (predominantly depression) over 6 months. We examined how lack of knowledge, prejudice and discrimination impacted on self-identification as having a mental illness, perceived need, intention to seek help, and help-seeking,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
108
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 147 publications
(129 citation statements)
references
References 53 publications
12
108
1
8
Order By: Relevance
“…Causes for the treatment gap are multi-faceted, and include affected individuals, clinicians and societal factors [6,7]. Awareness of mental health symptoms and relating them to a potential mental health problem has been shown to be an important predictor of perceived need and help-seeking intentions in persons with untreated mental disorders [8]. However, there is no existing evidence assessing the extent of the treatment gap in the Czech Republic.…”
Section: Introductionmentioning
confidence: 99%
“…Causes for the treatment gap are multi-faceted, and include affected individuals, clinicians and societal factors [6,7]. Awareness of mental health symptoms and relating them to a potential mental health problem has been shown to be an important predictor of perceived need and help-seeking intentions in persons with untreated mental disorders [8]. However, there is no existing evidence assessing the extent of the treatment gap in the Czech Republic.…”
Section: Introductionmentioning
confidence: 99%
“…As outlined in the introduction, selfidentification seems particularly relevant for help-seeking for mental disorders (Zimber et al, 2018), and is not well represented in general help-seeking theories such as the TPB, CSM or HBM. A longitudinal analysis of the present data showed that self-identification was strongly related to perceived need, which in turn was related to help-seeking intentions, which predicted help-seeking over six months, all contributing to a significant indirect effect of self-identification on help-seeking (Schomerus et al, 2018). Self-identification thus seems to be an important addition to established theories of help-seeking for mental disorders.…”
Section: Discussionmentioning
confidence: 45%
“…Details about our sampling method have been described in more detail elsewhere (e.g. Schomerus et al, 2018;Stolzenburg et al, 2017). Briefly, in order to recruit a community sample of currently untreated individuals with mental health problems, we used newspaper advertisements, social media posts and flyers in which we described several symptoms of depression without the 6 6 use of psychiatric wording or terminology, and invited those who had similar symptoms to call our study center (Stolzenburg et al, 2017).…”
Section: Study Design and Samplementioning
confidence: 99%
“…In this German group, personal stigmatising attitudes were associated with lower self-identification, while higher mental health literacy and having been previously treated for mental health problems seemed to facilitate greater self-perception as having a mental illness. Higher self-identification at baseline also predicted help-seeking from a mental health professional during a 6-months follow-up period [7]. …”
Section: Discussionmentioning
confidence: 99%
“…Individuals who do not recognise their difficulties as mental health problems do not direct their help-seeking towards mental health services [6]. Indeed, personal appraisal of one’s own mental health was shown to be a key predictor of perceived need for help among a community sample of adults meeting criteria for depressive disorder [5] and of subsequent help-seeking behaviour in a prospective study of persons with untreated mental illness [7]. Self-appraisal of having a mental illness could also be an important link which mediates the relationship between personal stigma and service use.…”
Section: Introductionmentioning
confidence: 99%